Sistem Teknologi Informasi dalam Mendukung Operasional Bank Syariah Modern - Al Ramzy; Parulian Sibuea; Zulfahri Salim; Salwa Latipah; Putri Ramadani (Universitas Muhammadiyah Surabaya, 2024)
Digital transformation has become a key driver in the changing landscape of the global financial industry, including Islamic banking. With the advancement of information technology, financial institutions strive to improve operational efficiency and provide better services to customers. This transformation includes not only the adoption of new technologies, but also changes in organizational culture and ways of interacting with customers.In this study using qualitative data types. The data source taken in this research is secondary data, where the data is obtained from literature both in the form of journals and reference books by studying, understanding, and examining things related to topics relevant to information systems can be understood as components that are integrated and interconnected in achieving certain goals, while information technology functions as a tool for producing, processing, and disseminating information to support company operations. In Islamic banking, information systems and technology play an important role in improving operational efficiency, service innovation, and compliance with sharia principles.